2009
DOI: 10.1590/s1984-82502009000200019
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of an electroanalytical methodology for determination of isoniazid and rifampicin content in pharmaceutical formulations

Abstract: Tuberculosis remains a major public health problem, especially in developing countries. Brazil presents the largest number of cases in Latin America and is among the 22 countries considered priorities by the World Health Organization (WHO). The Rio de Janeiro state has the largest number of cases registered in the country. The treatment of patients, commonly, makes use of the drugs isoniazid and rifampicin for six months. This study aimed to develop and validate an electroanalytical methodology, using the tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 13 publications
0
4
2
Order By: Relevance
“…The results of RIF obtained in the direction of reduction in Table 3 showed that the wider linear range was in this study compared to the studies in the literature. 21,37,38 Although carbon paste electrode gave a wider linear range in 22 , LOD value was higher than in this study. In 36 , there was no information about the linear range and the value of LOD was at the nM level as in this study.…”
Section: Comparison Of the Proposed Methodscontrasting
confidence: 56%
See 1 more Smart Citation
“…The results of RIF obtained in the direction of reduction in Table 3 showed that the wider linear range was in this study compared to the studies in the literature. 21,37,38 Although carbon paste electrode gave a wider linear range in 22 , LOD value was higher than in this study. In 36 , there was no information about the linear range and the value of LOD was at the nM level as in this study.…”
Section: Comparison Of the Proposed Methodscontrasting
confidence: 56%
“…In 36 , there was no information about the linear range and the value of LOD was at the nM level as in this study. The detection limits of the other studies in Table 3 37,38 were higher compared MWCNT/GC electrode in this study.…”
Section: Comparison Of the Proposed Methodscontrasting
confidence: 42%
“…The anti-TB treatment very often involves the administration of RIF together with other drugs, like ISN and PYR. Therefore, the selectivity and the sensitivity of analytical methods are compulsory features for simultaneous determination of the drugs in both pharmaceuticals and more complex matrices, like biological samples [ 18 , 56 , 68 , 69 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 ]. RIF bioavailability and, therefore, its therapeutic action can be influenced by its physical or chemical interactions with other molecules (peptides, DNA, drugs, nutrients, etc.).…”
Section: Rifamycins Detection and Monitoringmentioning
confidence: 99%
“…RIF cathodic behavior was investigated and exploited in qualitative analysis using mercury electrodes such as DME [ 70 ], SMDE [ 34 ] and HMDE [ 25 , 56 , 83 , 104 ]. RSV quantification by adsorptive stripping voltammetry at HMDE was also reported [ 105 ].At mercury electrodes, RIF voltammograms presented two peaks assigned to the irreversible reduction of the azomethine (−C=N−) functional group from the side chain of the 3-[(4-methyl-1-piperazinyl) imino] methyl moiety, which is more easily reducible and generates the more intense signal observed at less negative potentials (~0.95 V at pH ~7.00), and of the carbonyl group (situated at ~1.20 V at pH ~7.00), respectively [ 34 , 83 ].…”
Section: Rifamycins Detection and Monitoringmentioning
confidence: 99%
“…A comparison of the prepared electrode with other reported electrodes for the simultaneous determination of RIF and INZ 42,43,[52][53][54] is summarized in Table 1. It can be seen that Ni(OH)/rGO/SPCE has a lower or similar detection limit in most cases.…”
Section: Optimization Of Experimental Conditionsmentioning
confidence: 99%